GAMBARAN KARAKTERISTIK LUKA BERDASARKAN SKOR MUNGS DAN ANKLE BRAKHIAL INDEKS (ABI) PADA PASIEN DIABETES MELLITUS DENGAN ULKUS DIABETIK - Dahlia; Hussani; Makmun; Efriliana; Diani, Noor; Paulina, Paula; Fadiah, Elyana; Nurjanah, Siti; Permatasari, Winda (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2019)
Management of foot ulcers is one of them by ensuring an adequate blood supply that can be seenfrom the ABI value and caring for local injuries that can be seen from the MUNGS Score for theprevention of worsening and repair of wounds in people with DM. This study aims to describe theABI value and the characteristics of the injury based on the instrument to study the MUNGSinjury for diabetics with diabetic wounds. This research method in the form of quantitativedescription through interviews with guidelines. The sampling technique was accidental samplingand the sample size was 32 patients with type 1 and type 2 diabetes mellitus patients with diabeticulcers. The results of this study indicate that the ABI score in diabetes mellitus respondents withdiabetic ulcers has a mild score of 19 people (59%) and a wound assessment score (MUNGS) ofthe moderate category (6-10) of 17 people (53%). The higher the MUNGS value and the ABIvalue is far from normal, the injury condition is bad, and the lower the score and the ABI value isclose to normal, the better the wound condition.